2022
DOI: 10.1111/acel.13654
|View full text |Cite
|
Sign up to set email alerts
|

Genetic trade‐offs between complex diseases and longevity

Abstract: Longevity was influenced by many complex diseases and traits. However, the relationships between human longevity and genetic risks of complex diseases were not broadly studied. Here, we constructed polygenic risk scores (PRSs) for 225 complex diseases/traits and evaluated their relationships with human longevity in a cohort with 2178 centenarians and 2299 middle‐aged individuals. Lower genetic risks of stroke and hypotension were observed in centenarians, while higher genetic risks of schizophrenia (SCZ) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 104 publications
(136 reference statements)
0
4
0
Order By: Relevance
“…It has been reported that Dro and CecA1 expression can increase the lifespan in Drosophila (Loch et al, 2017). JBs had higher Dro , while FEJs had higher CecA1 and FLJs had non‐significantly higher CecA1 compared to JBs thus possibly explaining the comparable longevities of FLJs and JBs reported in Sharma and Shakarad (Sharma & Shakarad, 2021); besides, longevity is itself a polygenic trait (Hu et al, 2022; Tesi et al, 2020). Taken together, our results suggest that the FLJs have evolved to have an increased basal melanization response, evidenced by more crystal cells and higher PPO levels and PO activity than the ancestral JBs (though this difference was not always statistically significant).…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that Dro and CecA1 expression can increase the lifespan in Drosophila (Loch et al, 2017). JBs had higher Dro , while FEJs had higher CecA1 and FLJs had non‐significantly higher CecA1 compared to JBs thus possibly explaining the comparable longevities of FLJs and JBs reported in Sharma and Shakarad (Sharma & Shakarad, 2021); besides, longevity is itself a polygenic trait (Hu et al, 2022; Tesi et al, 2020). Taken together, our results suggest that the FLJs have evolved to have an increased basal melanization response, evidenced by more crystal cells and higher PPO levels and PO activity than the ancestral JBs (though this difference was not always statistically significant).…”
Section: Discussionmentioning
confidence: 97%
“…We also found that greater CAAG was associated with an increased risk of epilepsy, hypertension and dyslipidemia in individuals with high GRS of longevity. One possible explanation for this is that low GRS of longevity was associated with higher prevalence of metabolic disorders and higher genetic risks of epilepsy, hypertension and dyslipidemia were detected in long‐lived individuals (Hu et al., 2022 ). Metabolomic age provides different prediction values of some chronic diseases between diet, education, metabolic disorders, age or GRS groups.…”
Section: Discussionmentioning
confidence: 99%
“…PRS are the weighted scores of independent variations that represent the genetic risk to develop a phenotypic characteristic. PRS for longevity can serve as a proxy indicator of biological aging as higher PRS for longevity might forecast a slower biological aging process and are associated with an increased likelihood of longevity 45 whereas high PRS of life-threatening diseases are often associated with decreased odds of longevity 46 . High PRS for longevity is associated with an increased likelihood of healthy cognition aging and longer survival 47 and is negatively associated with metabolic syndrome 48 and brain aging process 49 .…”
Section: Aging Biomarkersmentioning
confidence: 99%
“…The ES is often gotten from a discovery GWAS 21 . Other variations of the classical method of PRS 46 , 97 have been proposed and software was developed to facilitate PRS calculation 98 . The step-by-step construction of polygenic scores has been reviewed in a recent study 99 .…”
Section: Other Measures Of Biological Agingmentioning
confidence: 99%